Chylothorax: report of a case complicating ductus ligation through a median sternotomy, and review. Issue 5 (October 1976) - Kaul, T K; Bain, W H; Turner, M A; Taylor, K M
Abstract : An unusual case of chylothorax is described in a 4-year-old child after repair of a ventricular septal defect and ligation of a patent ductus arteriosus through a median sternotomy. Left chylothorax developed after a latent period of six days and was treated initially with continuous drainage and parenteral supplementation of proteins and lipids. Operative intervention with oversewing of the site of the leak in the anterior mediastinum proved necessary after three weeks. The anatomical variations of the thoracic duct are outlined to explain the occurrence of chylothorax after diverse intrathoracic operations. The physiological effects of a thoracic duct fistula and various aspects of management are reviewed.